2012
DOI: 10.1002/14651858.cd004705.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical risk assessment as an aid for smoking cessation

Abstract: There is little evidence about the effects of most types of biomedical tests for risk assessment on smoking cessation. Of the fifteen included studies, only two detected a significant effect of the intervention. Spirometry combined with an interpretation of the results in terms of 'lung age' had a significant effect in a single good quality trial but the evidence is not optimal. A trial of carotid plaque screening using ultrasound also detected a significant effect, but a second larger study of a similar feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 102 publications
0
64
0
Order By: Relevance
“…More broadly, a recent Cochrane review of research on behavioral effects of providing genetic risk information identified effects on self-reported diet and intentions to change behavior, but little or no effects on actual behavior change for smoking and physical activity. 47,48 Notably, the included studies were generally of poor quality and underpowered to detect what are likely to be small effects. In addition, potential negative behavioral effects of providing genetic risk information have not been rigorously studied.…”
Section: Conceptual Domainsmentioning
confidence: 99%
“…More broadly, a recent Cochrane review of research on behavioral effects of providing genetic risk information identified effects on self-reported diet and intentions to change behavior, but little or no effects on actual behavior change for smoking and physical activity. 47,48 Notably, the included studies were generally of poor quality and underpowered to detect what are likely to be small effects. In addition, potential negative behavioral effects of providing genetic risk information have not been rigorously studied.…”
Section: Conceptual Domainsmentioning
confidence: 99%
“…Some physiological measures such as exhaled carbon monoxide (CO) return to non-smoker levels within a few days of quitting smoking, and lung function improves within months of quitting (Bize et al, 2012; Scanlon et al, 2000; Jang et al, 2010). It has been suggested that providing smokers with feedback on biomedical tests and the possible future effects of smoking and quitting on such test results may be a strategy for increasing smoking cessation rates (Bize et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that these new item banks will be particularly useful in helping identify individuals who are ready to quit smoking and might respond to a brief intervention by a primary care provider (e.g., motivational interview). It is also plausible to envision that measurement of this construct could help fine tune smoking-related intervention strategies that attempt to capitalize on the relationship between health-related outcome expectancies and smoking behavior (Bize et al, 2012;Schlam & Baker, 2013). Preliminary validity of the health expectancies scores is evaluated in a separate paper in this issue (Edelen, Stucky, et al).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, health-related outcome expectancies (or perceived health risks and benefits) are also fundamental constructs of many health behavior theories (Brewer et al, 2007;Weinstein, 1993), and smokers' healthrelated outcome expectancies of smoking and quitting are associated with a number of smoking-related constructs, such as intentions to smoke, decisions to start smoking, decisions to quit, and successful periods of abstinence (McKee, O'Malley, Salovey, Krishnan-Sarin, & Mazure, 2005;Romer & Jamieson, 2001;Weinstein, 2001). Many smoking-related intervention strategies capitalize on the relationship between health-related outcome expectancies and smoking behavior (Bize et al, 2012;Schlam & Baker, 2013). A common approach in public health interventions targeting smoking prevention or cessation is use of fear appeals to increase perceptions of health threat and downstream to change smoking behavior (Witte & Allen, 2000).…”
Section: Introductionmentioning
confidence: 99%